Educational Values in the Novel Pukul Setengah Lima by Rintik Sedu - Ikhwan, Wahid Khoirul; Rosid, Abdul; Karim, Muhammad Busyro; Setyawan, Arief (Literasi Nusantara, 2026)
This study aims to describe the educational values embedded in the novel Pukul Setengah Lima by Rintik Sedu. The research employs a qualitative method with a narrative approach, as the data consist of literary narratives and textual descriptions that are analyzed in depth. The data source is the novel Pukul Setengah Lima, with data units in the form of words, phrases, sentences, and paragraphs relevant to the focus of the study. Data collection techniques include library research, close reading, and note-taking. Data analysis is conducted using an objective hermeneutic method to interpret textual meanings in a systematic and objective manner.The findings indicate that Pukul Setengah Lima contains various educational values, encompassing individual, social, and religious values. The identified individual values include patience, loyalty, honesty, sacrifice in love, filial piety, and compassion. Social values comprise mutual respect, openness, and a sense of family. Meanwhile, religious values include faith in God, belief in divine decree (qada and qadar), and the value of prayer. These educational values demonstrate that the novel is relevant as a medium for character education and can be utilized in language and literature learning. Therefore, this literary work has the potential to serve as an effective educational medium in strengthening educational values within academic contexts